Perang Utang pada Hubungan Kepemilikan Institusional dengan Penjualan Pihak Berelasi. - Ermad M.J; Fathul Khaira; Dhea Adhima Suemdra (Jurnal EMT KITA, 2022)
This study aims to examine the role of debt in moderating the effect of institutional ownership on sales to related parties. This research is a sample study, which includes 300 companies from 706 manufacturing sector companies during the 2017-2020 observation year. The sample was selected with certain criteria techniques. The analytical method used is moderated regression analysis. The results of the study found that institutional ownership has a significant positive effect on sales to related parties. Debt is not able to moderate the effect of institutional ownership on sales to related parties.